2015
DOI: 10.1179/1362171815y.0000000036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tool pin features on process response variables during friction stir welding of dissimilar aluminum alloys

Abstract: In this paper, the effect of pin features and orientation/placement of the materials on advancing side were investigated for friction stir welding (FSW) of dissimilar aluminum alloys AA2050 and AA6061. Pins for FSW were produced with a 2?12 mm pitch thread having three flats/flutes. Three sets of rotational speed/welding speed were used to perform a series of welds in a butt joint arrangement. The results show that, joint quality, process response variables and welding temperature are highly affected by pin fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Evidence of fine grain size, fine distribution of Si particles and reduced residual stresses in the SZ were found for low rotation and welding speeds. Together with rotation and welding speeds, the effect of tool geometry like the pin profile or features [14,18,47,48,62], pin shapes [34,57] and shoulder diameter to pin diameter ratio [37,60] on joint strength have been investigated. The pin profile or feature controls material flow and in effect material mixing at the joint interface, the pin shape affects SZ size as well as material movement and the shoulder to pin diameter ratio controls frictional heat generation between the tool and the BM.…”
Section: Tensile Strengthmentioning
confidence: 99%
“…Evidence of fine grain size, fine distribution of Si particles and reduced residual stresses in the SZ were found for low rotation and welding speeds. Together with rotation and welding speeds, the effect of tool geometry like the pin profile or features [14,18,47,48,62], pin shapes [34,57] and shoulder diameter to pin diameter ratio [37,60] on joint strength have been investigated. The pin profile or feature controls material flow and in effect material mixing at the joint interface, the pin shape affects SZ size as well as material movement and the shoulder to pin diameter ratio controls frictional heat generation between the tool and the BM.…”
Section: Tensile Strengthmentioning
confidence: 99%
“…Since recent publications do not give definitive direction as to the optimal weld configuration (i.e., the placement of the alloy on the retreating or advancing side), the examined joints were produced in two configurations. Some researchers [10,14,28,29] reported that when the weaker alloy is placed on the retreating side, the produced weld becomes weaker compared to the opposite configuration. However, according to other investigations [12,13,30], the more efficient mixing of materials and better properties can be achieved with the softer alloy on the advancing side and the harder alloy on the retreating side.…”
Section: Effect Of Alloy Configurationmentioning
confidence: 99%
“…Therefore, many investigations have focused on the parameters of the FSW process and their effect on properties and microstructure of welds. Influence of tool rotational speed [6][7][8][9], welding speed [7][8][9][10][11], configuration of welded alloys [10,12], and pin geometry [6,[13][14][15] on welding of dissimilar aluminum alloys has been extensively examined to date.…”
Section: Introductionmentioning
confidence: 99%
“…Tool properties such as geometry play a critical role in determining material flow and it controls what is the optimal transverse speed for good quality weld formation [38,39]. The tool is designed with a shoulder and a pin, as shown in Figure 1 and it has two main functions: to control the material flow and generate heat.…”
Section: Tool Propertiesmentioning
confidence: 99%